Perlindungan Hak Anak Pra Isbat Nikah Ditinjau Dari Hukum Positif - Fakhrurrazi M. Yunus; Dwi Oktavia (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2023)
Protecting children is difficult to do without official registration of the child's birth, because the parents got married without having an official marriage record in the regulations of the Republic of Indonesia, in the sense that it has not been recorded at the KUA. However, the marriage is valid according to religious views because it has fulfilled the pillars and conditions of marriage in accordance with the guidance of the Shari'ah. The formulation of the problem that will be answered in this study is how the protection of children before Proofing of marriage is reviewed through positive law in the decision of the syar'iyah court, Case Number 40/Pdt.P/2021/MS.Bna, and what is the method of finding the judge's law regarding the granting of requests for ratification of the child's lineage from couples who don’t have Proof of marriage, while the aim is to analyze the protection of children before Proofing of marriage if viewed according to positive law and analyze the judge's legal methods in granting the ratification of the lineage of children from couples who don’t have Proof of marriage. This study uses qualitative methods with a normative juridical approach. The data collection method was carried out using the library research method, data analysis was carried out in a normative descriptive way. This study concludes that every child has the right to protection and obtains his rights, one of which is identity and citizenship status. A child's identity must be given from birth, which is stated in the birth certificate (vide Article 5, Article 7, paragraph (1) and Article 27 paragraph (1) and (2) of Law Number 23 of 2002 concerning Child Protection. Discovery method There are three judges' laws; referring to the Islamic legal doctrine contained in the book Al Fiqhu Al Islami Wa Adillatuhu, referring to the provisions of Article 55 Paragraph (3) of Law Number 1 of 1974 concerning marriage juncto Article 103 Paragraph (3) Compilation of Islamic Law in Indonesia and in Article 47 of Law Number 23 of 2006 concerning Population Administration.